Future images of youth on food systems transformation– study with the Finnish high school students - Kaljonen, Minna; Varho, Vilja; Sonck-Rautio, Kirsi; Ritola, Roosa; Savikurki, Anni (Elsevier, 2025)
Although youth have been recognized as an increasingly important group in sustainable development, their participation in the existing practices of food policy and societal decision-making is still limited. This paper analyses future images of youth to better understand how young people assess future trajectories of food systems, and what they see important in terms of sustainability. The future images were collected as essays from 123 high school students from Finland. The results comprise of six different future images: BAU+ , conscious consumer, back to the roots, strict regulation, technology solves sustainability problems and food for survival. The future images of youth question the continued growth narrative by emphasizing technological transformation, consumer responsibility and local food systems as solutions to sustainability problems. Dystopian image is also present in the future images of youth, calling attention to issues worth saving in our current food systems. The exploration of the future images of youth contributes to the Dator’s future typology contextualizing them to the food systems. The results point towards strengthening of futures literacy both in food policy and in education. Futures literacy is needed to act upon challenges faced in a more inclusive manner, whilst building agency in the meantime.
Keywords: tulevaisuudentutkimus; nuoret; ruoka; tulevaisuuskasvatus; future images; food systems transformation; youth; futures literacy